Development and Validation of EFL Speaking Strategy, Speaking Anxiety, Learning Motivation, and Learning Attitude Questionnaires - Wenxin, Lu; Joseph, Ramanair (I.K. Press, 2025)
Effectively assessing the speaking performance of English as a Foreign Language (EFL) students remains a major challenge for language educators, particularly in the context of Chinese universities. Speaking strategy use, speaking anxiety, learning motivation, and learning attitude are four critical constructs that significantly influence EFL learners’ speaking proficiency. While previous studies have examined these factors individually or in limited combinations, few have focused on developing a comprehensive tool that measures them collectively within the Chinese EFL context. Therefore, this pilot study aimed to develop and validate a questionnaire, designed to assess speaking strategies, speaking anxiety, learning motivation, and learning attitudes among Chinese EFL students, which consist of 45, 30, 22 and 49-items scale for each respectively. The purpose of this pilot test was to ensure the reliability and validity of the instrument before it is used in a larger-scale study. The questionnaire was assessed by surveying on 60 participants selected from 1st and 2nd year non-English major undergraduate students at a university in China, with a sample of 27 males and 33 females, along with 34 freshmen and 26 sophomores. A five-phase approach was followed: item development based on literature review, definition of constructs, expert validation by two applied linguistics scholars, and a pilot administration involving 60 first- and second-year Chinese university students. The results showed strong content validity and high internal consistency, with a reliability value of 0.787 for speaking strategies, 0.674 for speaking anxiety, 0.775 for learning motivation, and 0.796 for learning attitudes, making the questionnaire highly reliable and valid tool for future research. This study offers a valuable instrument for educators and researchers to investigate the interconnected roles of these key psychological and behavioral factors in EFL speaking development, particularly within the Chinese academic context.